2022
DOI: 10.1186/s12880-022-00848-9
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography imaging features of malignant ‘triton’ tumor to facilitate its clinical diagnosis: report of two cases

Abstract: Background Malignant ‘triton’ tumor is an extremely rare subtype of malignant periphery nerve sheath tumors. Clinical diagnosis of malignant triton tumor is difficult before surgery due to its low incidence and the lack of knowledge. Therefore, to describe and summarize the CT imaging characteristics of malignant triton tumor is of great assistance for early and preoperative diagnosis. Case presentation Two cases suspected of MTT by CT scan before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We compiled data on reported cases of MTT in the recent 6 years (2018–2023, Table 1). 1,6–38 There were totally 37 cases with a mean age of 39.4 years (range 8 months old–75 years old), including 24 male and 13 female patients. Eleven cases originated in the abdomen (30%), 10 cases in the head and neck (27%), 8 cases in the thoracic cavity (21%), 6 cases in the limbs (16%), 1 case in the spine (3%), and 1 case in the buttocks (3%).…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We compiled data on reported cases of MTT in the recent 6 years (2018–2023, Table 1). 1,6–38 There were totally 37 cases with a mean age of 39.4 years (range 8 months old–75 years old), including 24 male and 13 female patients. Eleven cases originated in the abdomen (30%), 10 cases in the head and neck (27%), 8 cases in the thoracic cavity (21%), 6 cases in the limbs (16%), 1 case in the spine (3%), and 1 case in the buttocks (3%).…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…A range of cases presentation in the literature we reviewed describe the imaging manifestations (including CT and MRI) correlated with MTT: giant lump, heterogeneity, irregular margins, intratumoral hemorrhage, necrosis, lobulation, calcifications, heterogenous enhancement on postcontrast CT or MRI, hypointense/isointense T1WI and hyperintense T2WI signal on MRI, and diffusion restriction on DWI and ADC 1,8–32,39,40 . Zain et al 20 and Li et al 29 had reported similar conclusions, Li et al pointed out some characteristics common to MTTs and MPNSTs, including ill‐defined margin, intratumoral lobulation, peripheral edema, calcifications, and destruction of adjacent bone tissues. In our case, it manifested as a heterogeneous giant mass with unclear border in ultrasonography, long T1 and T2 signals on MRI, marginal lobulation, and multiple metastases on PET‐CT.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical or radiological suspicion is very difficult due to the scarcity of these tumors. Based on CT analysis, Li Y et al summarized the reference clinical characteristics for the diagnosis of MTT: (i) an enormous mass-like shadow; (ii) a well-circumscribed lobulated shape; and (iii) a well-defined mass with hemorrhages, necrosis, cystic changes and calcification, especially within NF-1 patients ( 21 ). In our case, the MTT mimicked hepatocellular carcinoma on MRI and CT, where an enhancement pattern was observed as fast-in and fast-out.…”
Section: Discussionmentioning
confidence: 99%